PERKEMBANGAN SISWA SMK KELAS X DALAM PEMBELAJARAN OPERASI BILANGAN - Padhila Angraini; Rully Charitas Indra Prahmana; Ardhi Ardhian (IKIP Siliwangi, 2018)
This study aims to determine about the development of students. This research method used is Single Subject Research (SSR) with basic design of A-B. The techniques of data collection used observation and interview to determine difficulties and the ability understanding mathematical students. The results of this study indicate that kontruktivisme approach can improve understanding mathematical students. It can be seen from the average score obtained by the student before the treatment given that is 11,75 and increased to 77,88 after treatment.